Monitoring data on the effect of domestic livestock and rabbits on Androcymbium europaeum (Lange) K. Richt. and its xerophytiques pastures for thirteen years - Antonio Jesús Pérez-Luque; María Eugenia Ramos-Font; Mauro José Tognetti Barbieri; Clara Montoya Román; Claudia Tribaldos Anda; Francisco M. Cabezas-Arcas; José González-Rebollar; Ana Belén Robles (Biodiversity Data Journal, 2024)
Dataset of annual monitoring of herbivory effects on the conservation status of the endangered species Androcymbium europaeum (Lange) K. Richt and its associated plant communities is presented in this manuscript. This dataset encompasses the annual monitoring of herbivory effects on the conservation status of the endangered species Androcymbium europaeum. Since 2010, the SERPAM Department (Service of Evaluation, Restoration and Protection of Mediterranean Agrosystems) at the Zaidin Experimental Station, belonging to the Spanish National Research Council (CSIC-EEZ), has conducted annual sampling to assess the impact of both domestic and wild livestock, specifically rabbits, on the pastures where A. europaeum lives. The study consisted of a randomised block design, implementing three distinct treatments to evaluate different management strategies: (1) rabbit and domestic herbivory, (2) exclusion of domestic livestock and (3) exclusion of rabbits and domestic livestock. Within each treatment, two types of monitoring were conducted. Firstly, the abundance of A. europaeum was estimated by counting individuals within 50 cm x 50 cm quadrats. Secondly, plant species diversity was assessed along 2-m long transects using the modified Point-Quadrat method. The research was conducted within the Cabo de Gata-Níjar Natural Park in southern Spain, specifically in the Amoladeras Nature Reserve in Almería.The dataset contains information spanning from 2010 to 2023, providing valuable insights into the annual monitoring of herbivory effects on the conservation status of A. europaeum, contributing to our understanding of the species' interaction with domestic and wild animal in the studied area.